Focus on long non-coding RNA MALAT1: Insights into acute and chronic lung diseases - Lai, Xingning; Zhong, Jie; Zhang, Aihua; Zhang, Boyi; Zhu, Tao; Liao, Ren (Frontiers in Genetics, 2022)
Acute lung injury (ALI) is a pulmonary illness with a high burden of morbidity and mortality around the world. Chronic lung diseases also represent life-threatening situations. Metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) is a type of long non-coding RNA (lncRNA) and is highly abundant in the lung tissues. MALAT1 can function as a competitive endogenous RNA (ceRNA) to impair the microRNA (miRNA) inhibition on targeted messenger RNAs (mRNAs). In this review, we summarized that MALAT1 mainly participates in pulmonary cell biology and lung inflammation. Therefore, MALAT1 can positively or negatively regulate ALI and chronic lung disease (e.g., chronic obstructive pulmonary disease (COPD), bronchopulmonary dysplasia (BPD), pulmonary fibrosis, asthma, and pulmonary hypertension (PH)). Besides, we also found a MALAT1-miRNA-mRNA ceRNA regulatory network in acute and chronic lung diseases. Through this review, we hope to cast light on the regulatory mechanisms of MALAT1 in ALI and chronic lung disease and provide a promising approach for lung disease treatment.